Perovskite and Piezoelectric Materials - Pola, Someshwar; Panwar, Neeraj; Coondoo, Indrani; Pola, Someshwar; Panwar, Neeraj; Coondoo, Indrani (IntechOpen, 2021)
Investigating in the area of perovskite materials and the fabrication of devices for properties in optoelectronics, we have presented a brief outline of perovskite materials. The authors present a fairly comprehensive arrangement of this very active area of research, with its past changes and present position and outlooks. Discussions are presented regarding photocatalysis, fabrication of solar cell devices and their stability, lead-free materials, as well as thermoelectric and piezoelectric applications. In view of the present status of perovskite materials, I am assured that each chapter of the book will be of boundless encouragement for researchers, scientists, and academicians working in this field.
English
Keywords: Condensed matter physics (liquid state & solid state physics); Condensed matter physics (liquid state & solid state physics)